Examination of Endoparasite Presence in Threadfin Bream Fish at the Tegal Kamulyan Fish Auction Place - Putra, Rey Defta Arma; Muhammad, Andira Maulana; Wardani, Figo Pamilu; Fath, Muhammad Syafiq Zain Al; Munashe, Mawoyo; Pratama, Ikhsan (Proceedings Series on Social Sciences & Humanities, 2025)
This study aimed to observe and identify the presence of endoparasites, specifically the parasite Anisakis sp., in threadfin bream fish (Nemipterus japonicus) obtained from the Tegal Kamulyan fish auction place, Cilacap. Threadfin bream is a consumable fish with the potential for parasitic infection that can impact human health. Fish samples were randomly collected and examined visually as well as through dissection of the digestive tract to detect parasites. The results showed that out of 12 fish samples, 3 samples were positively infected by Anisakis sp., found in the stomach and intestines. The parasite is 1-2 cm in size, milky white in color, and can cause digestive tract disturbances in fish as well as pose a health risk to humans if consumed without proper processing. Therefore, the recommendation given is to ensure fish is cooked thoroughly and to perform selection of raw fish materials to avoid parasitic infection. This study highlights the importance of fish quality control to maintain food safety and public health.